PENGUATAN KARAKTER SISWA MELALUI INTEGRASI NILAI-NILAI PANCASILA PADA PENDIDIKAN KEWARGANEGARAAN DI SEKOLAH DASAR - Asrofah, Fitrika Lailatul; Radeni Sukma Indra Dewi; Intan Sari Rufiana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study investigates the reinforcement of student character through the integration of Pancasila values and Civic Education in elementary schools. The problem addressed in this research is the limited implementation of character education that meaningfully connects philosophical national values with classroom practices. The study aims to identify how Pancasila principles can be systematically embedded into Civic Education learning and how this integration contributes to the development of students’ moral, social, and civic competencies. Using a qualitative descriptive methodology, data were collected through classroom observations, teacher interviews, and document analysis in three public elementary schools. The findings show that character strengthening becomes more effective when Pancasila values are explicitly linked with daily learning activities, contextual issues, and collaborative classroom tasks. Teachers who apply inquiry-based discussions, project-based assignments, and reflective learning strategies demonstrate higher success in cultivating responsibility, cooperation, critical thinking, and national identity among students. The study concludes that integrating Pancasila values into Civic Education not only enhances students’ understanding of civic responsibilities but also fosters consistent character growth aligned with Indonesia’s national ideology. These results highlight the importance of intentional planning, innovative pedagogy, and teacher competency development to ensure that character education becomes a transformative part of elementary learning.